PERAN PSIKOLOGI PENDIDIKAN TERHADAP PERMASALAHAN BELAJAR SISWA - Mohammad Erlangga (INCARE, International Journal of Educational Resources, 2022)
Educational psychology has a very important role for an educator as knowledge to understand the characteristics of students. The study of educational psychology is used to analyze students' learning problems. This research is a complement by focusing on the research subject who is a student as well as a student at a boarding school in Bondowoso. Descriptive qualitative as the method chosen to analyze the data. so that the learning problems experienced by students who are also students are obtained. The scope of educational psychology makes it easier for teachers to help overcome these learning problems.